2017
DOI: 10.3390/su9040584
|View full text |Cite
|
Sign up to set email alerts
|

Evolution Characteristics of Landscape Ecological Risk Patterns in Coastal Zones in Zhejiang Province, China

Abstract: Analyzing evolution characteristics of landscape ecological risk patterns would help establish ecological risk early warning mechanism, reduce the ecological risk probability and promote coastal landscape pattern optimization. In this study, landscape pattern indices were first calculated by using multitemporal Landsat TM images acquired in years 1990, 2000 and 2010, then landscape ecological risk pattern evolution models and the spatiotemporal evolutions of ecological risk patterns of coastal zones in Zhejian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 33 publications
3
42
0
Order By: Relevance
“…Here, a , b and c are the weights of indices, set to 0.5, 0.3 and 0.2 according to their importance [20]. Fragmentationi=NLiTAi…”
Section: Methodsmentioning
confidence: 99%
“…Here, a , b and c are the weights of indices, set to 0.5, 0.3 and 0.2 according to their importance [20]. Fragmentationi=NLiTAi…”
Section: Methodsmentioning
confidence: 99%
“…Land use is one of the most intuitive expression forms of humans developing and using the physic-geographical environment [49,50]. Structural or pattern changes of land are highly correlated with spatial and temporal distribution and dynamics of landscape ecological risk [60]. Land use changes not only influence single ecological elements like soil environment, atmospheric environment, and water environment, but also affect maintaining the comprehensive ecological process and environmental evolution in a basin, thus threatening ecological health and ecological security in the study area.…”
Section: Effects Of Land Use Changes On Ecological Risk In the Study mentioning
confidence: 99%
“…This kind of research also showed that the landscape change index was used as a way of monitoring landscape changes and therefore could be used for landscape ecological risk assessment [34]. A landscape pattern index is a true reflection of the regional landscape structure, layout, and function [35][36][37]. Under external disturbance, a landscape ecosystem tends to be broken or the stability is weakened, which can truly reflect the change in the landscape pattern index.…”
Section: Introductionmentioning
confidence: 99%
“…This method provided theoretical support for the enrichment of information in the process of quantifying regional ecological risk. As a basic evaluation unit for multiple data source integration, small watersheds can ensure the unity of ecosystem structure and processes while ensuring the heterogeneity of the natural environment of different evaluation units to avoid the fragmentation of natural geographical connections [13,47]. This risk unit segmentation method can be used to effectively analyze ecological risk patterns and accurately control risk management zoning.…”
Section: Discussionmentioning
confidence: 99%
“…where LLI k denotes the landscape loss index of a small watershed k; n is the number of landscape types; E i is the landscape disturbance index of landscape i; F i is the landscape vulnerability index of landscape i; S ki is the area of landscape components i in a small watershed k; and S k is the total area of a small watershed k. By referring to previous studies [21,24,46,47], the detailed calculation methods of E i and F i were given in Table 3. Table 3.…”
Section: Impairmentmentioning
confidence: 99%